2019
DOI: 10.1097/j.pain.0000000000001669
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for T-type calcium channels in homocysteinemia-induced peripheral neuropathy

Abstract: Homocysteinemia is a metabolic condition characterized by abnormally high level of homocysteine in the blood and is considered to be a risk factor for peripheral neuropathy. However, the cellular mechanisms underlying toxic effects of homocysteine on the processing of peripheral nociception have not yet been investigated comprehensively. Here, using a rodent model of experimental homocysteinemia, we report the causal association between homocysteine and the development of mechanical allodynia. Homocysteinemia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…Plasma homocysteine levels ranging from 15 to 30 μM cause mild hHcy, 31 to 100 μM—moderate hHcy or >100 μM—severe hHcy symptoms [ 23 ]. An elevated level of homocysteine induces endothelial dysfunctions, oxidative stress, or inflammation and is associated with several pathological states like neurological disorders, chronic kidney disease, osteoporosis, gastrointestinal disorders, cancer, or congenital defects [ 24 , 25 , 26 ]. Increased homocysteine levels during pregnancy result in preeclampsia, fetus pathologies or growth restriction due to endothelial dysfunctions of the placenta [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma homocysteine levels ranging from 15 to 30 μM cause mild hHcy, 31 to 100 μM—moderate hHcy or >100 μM—severe hHcy symptoms [ 23 ]. An elevated level of homocysteine induces endothelial dysfunctions, oxidative stress, or inflammation and is associated with several pathological states like neurological disorders, chronic kidney disease, osteoporosis, gastrointestinal disorders, cancer, or congenital defects [ 24 , 25 , 26 ]. Increased homocysteine levels during pregnancy result in preeclampsia, fetus pathologies or growth restriction due to endothelial dysfunctions of the placenta [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion was that hypertension was closely associated with HCY [9]. According to previous ndings, a high level of HCY did harm to systemic vascular endothelial cells [10,11]. Elsherbiny et al further demonstrated that HHCY can undermine inner and outer blood-retinal barriers [12].…”
Section: Discussionmentioning
confidence: 97%
“…HCY is converted to cysteine and eventually metabolizes in the body to produce H 2 S in the process. Accumulating evidence indicated that H 2 S is a physiological vasorelaxant and reduced production of H 2 S in the vascular tissue leads to hypertension [11,21,22]. Besides, HHCY may cause direct toxicity and vascular endothelial injury, which may induce hypertension or aggravating the damage of hypertension to vessels [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of Ca v 3.2 in primary afferent nociceptive fibers is causally linked to the development of peripheral painful neuropathy associated with nerve injury [18][19][20], antineoplastic drugs [21][22][23], inflammation [24,25], and diabetes [1,3]. Several studies have unraveled some of the mechanisms underlying the pathological expression of Ca v 3.2 and alteration of the posttranslational regulation of the channel including ubiquitinylation [26], SUMOylation [27] and phosphorylation [28,29]. Defects in these processes have emerged as some of the primary reasons leading to enhanced expression of the channel.…”
Section: Discussionmentioning
confidence: 99%